Giant Polycystic Papillary Renal Cell Carcinoma: A Case Report and Literature Review - Huang, Zhongming; Wang, Hai; Ji, Zhigang (Frontiers in Oncology, 2022)
Introduction: Giant, cystic renal tumors are generally considered relatively contraindicated for laparoscopic surgery. We report a 19-year-old male, who accidentally noted polycystic lesions in the left kidney by enhanced computed tomography (CT) by focusing on the diagnostic, clinical, and surgery to the patient. Case report: Enhanced CT scan revealed solid component in multiple cystic lesions of Bosniak IV, which was enhanced after injection of contrast agent, and the left kidney lost normal profile and enlarged with maximal diameter more than 18cm. Positron emission tomography-computed tomography (PET-CT) showed SUVmax 4.8 of the lesion and suggested malignant disease. A retroperitoneal laparoscopic radical left nephrectomy was performed successfully without cyst burst, and the lesion was 17×17×18 cm in size. Pathological examination revealed that the lesions were consistent with papillary renal cell carcinoma (type 2, WHO grade II), no renal capsule invasion, no renal pelvis and renal sinus fat involvement, no abnormality in ureter and renal arteriovenous end, no abnormality in a few adrenal tissues, chronic inflammation of hilar lymph nodes (0/1). After surgery, no specific treatment was initiated, and at a follow-up visit 1 years after surgery, no local recurrence or metastasis was found. Conclusion: It is the largest cystic renal cell carcinoma that has ever been reported for laparoscopic resection. The selection of surgery for giant cystic renal cell carcinoma should be individualized. Retroperitoneal laparoscopy may be an option for such lesions.